Heterogeneous Fenton process based on layered double hydroxides for urban wastewater treatment - Serge, Nayara de Melo Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The interest in the application of Layered Double Hydroxides (LDHs) as catalysts in heterogeneous Fenton has become frequent due to their interesting structural properties, low production cost, ease of synthesis, the possibility of incorporation of different types of elements in the same structure and application under neutral conditions. The improvement and use of these materials as catalysts in secondary treated urban wastewater (STWW), would bring benefits to human health and the environment. These perspectives motivated this study, where LDHs based on CuMgFe were synthesized for the activation of different oxidizing agents, hydrogen peroxide (H2O2), persulfate (PDS = S2O8 2-), and peroxymonosulfate (PMS = HSO5 -) in the generation of reactive species for the degradation of pharmaceuticals and inactivation of pathogens in STWW. Initially, two pyroaurite-type LDHs (MgFe-CO3 and CuMgFe-CO3) were synthesized by the coprecipitation method at constant pH to evaluate the influence of the insertion of Cu in the LDH on the degradation of the sulfathiazole antibiotic (STZ) in the dark and under LED-Vis irradiation. XPS analyzes confirmed the insertion of Cu(II) in the LDH structure and the presence of Cu(I), which increased the degradation efficiency of 150 μg L-1 of STZ, and achieving non detectable concentration was after 90 min using 4 mmol L-1 of H2O2 and 0.5 g L-1 of CuMgFe-CO3 at pH 7.5, under LED-Vis irradiation. In view of the potential of the LDH with copper to remove the antibiotic at a pH close to neutral and the high stability of the catalyst even after 4 cycles of reuse, it was decided to study the influence of the interlamellar anion on the activity. Four LDHs of CuMgFe were synthesized, with a variation of the interlamellar anion: B(OH)4 -, CO3 2-, NO3 - and SO4 2-, for the removal of the anticancer 5- fluorouracil (5-FU) in the dark and under solar radiation. XRD and XPS results showed the phase purity of the catalysts synthesized and the intercalation of the respective anions. The degradation process in the dark showed that the interlamellar anion has a strong effect on the catalytic properties of the LDH, showing the following pseudo-first order (k) rate constant sequence: CuMgFe-B(OH)4 > CuMgFe-NO3 > CuMgFe-SO4 > CuMgFe-CO3. The highest efficiency of LDH with boron was explained based on FTIR and XPS results, which showed the interactions B-O and B-OH, which were responsible for inducing modifications on the electronic density of CuMgFe-B(OH)4, accelerating the reduction of Cu(II) and Fe(III) and thus favoring the generation of reactive oxygen species in the Fenton process. This catalyst allowed the complete degradation of 200 μg L-1 of 5-FU under solar radiation after 20 min and after 40 min in the dark, with degradation efficiency maintained above 90% until the fourth cycle of use in the presence of 10 mmol L -1 H2O2 and 0.5 g L-1 LDH. The excellent performance of CuMgFe-B(OH)4 in the degradation of 5-FU, motivated the studies on the application of this catalyst in the simultaneous degradation of the antibiotics sulfamethoxazole (SMX), ciprofloxacin (CIP), cephalexin (CFX) and amoxicillin (AMX) and inactivation of Escherichia coli and Enterococcus faecalis pathogens with different oxidizing agents, H2O2, PDS, and PMS. In each system with different oxidants, CuMgFe-B(OH)4 behaved differently. LDH-activated PMS was the most efficient process and provided more than 90% removal of all antibiotics after 120 min and complete inactivation of pathogens using 0.5 g L-1 LDH and 4 mmol L-1 PMS. However, the LDH system with H2O2 was efficient for disinfection, but not for the degradation of antibiotics due to the formation of complexes between the cations present in the catalyst structure and H2O2. The PDS activated system occurred by a non-radical pathway involving mainly singlet oxygen (1O2) and Cu(III) with the removal of antibiotics, but limited disinfection capacity for Escherichia coli. In the experiments performed in this thesis, high stability of the synthesized LDHs and excellent performance under neutral conditions were observed, which is important for the application of these materials as catalysts.

O interesse na aplicação de Hidróxidos Duplos Lamelares (HDLs) como catalisadores no processo Fenton heterogêneo tem se tornado frequente devido às suas interessantes propriedades estruturais, baixo custo de produção, facilidade de síntese, possibilidade de incorporação de diferentes tipos de elementos em uma mesma estrutura e aplicação em condições de neutralidade. O aprimoramento e uso desses materiais como catalisadores no tratamento de efluente de uma estação de tratamento de esgoto (ETE), traria benefícios à saúde humana e ao meio ambiente. Estas perspectivas, motivaram a realização deste trabalho, onde foram sintetizados HDLs baseados em CuMgFe para a ativação de diferentes agentes oxidantes, peróxido de hidrogênio (H2O2), persulfato (PDS = S2O8 2-), e peroximonosulfato (PMS = HSO5 - ) na geração de espécies reativas para a degradação de fármacos e inativação de patógenos em efluente de ETE. Inicialmente foram sintetizados dois tipos de HDLs do tipo piroaurita (MgFe- CO3 e CuMgFe-CO3) pelo método de coprecipitação a pH constante para avaliar a influência da inserção de Cu no HDL na degradação do antibiótico sulfatiazol (STZ) no escuro e sob radiação LED-Vis. As análises de XPS confirmaram a inserção de Cu(II) na estrutura do HDL e a presença de Cu(I) após a reação, o que aumentou a eficiência de degradação de 150 μg L-1 de STZ, onde após 90 min de reação não foi possível detectar o contaminante utilizando 4 mmol L-1 de H2O2 e 0,5 g L-1 de CuMgFe-CO3, em pH 7,5, sob irradiação LED-Vis. Tendo em vista o potencial do HDL com cobre em remover o antibiótico em pH próximo ao neutro e a alta estabilidade mesmo após 4 ciclos de reuso, decidiu-se estudar a influência do ânion na atividade catalítica. Quatro HDLs de CuMgFe foram sintetizados, com variação do ânion interlamelar: B(OH)4 -, CO3 2-, NO3 - e SO4 2-, para a remoção do fármaco anticâncer 5-fluorouracil (5-FU) no escuro e sob radiação solar. Os resultados de DRX e XPS mostraram que os catalisadores foram sintetizados com pureza de fase e os respectivos ânions foram intercalados. A aplicação do processo de degradação no escuro, mostrou que o ânion interlamelar tem um forte efeito nas propriedades catalíticas do HDL, apresentando a seguinte sequência de constante de velocidade de pseudo-primeira ordem (k): CuMgFe-B(OH)4 > CuMgFe-NO3 > CuMgFe-SO4 > CuMgFe- CO3. A alta eficiência do HDL com boro foi explicada com base nos resultados de FTIR e XPS, que mostraram as interações B-O e B-OH, as quais foram responsáveis por induzir modificações na densidade eletrônica de CuMgFe-B(OH)4 , acelerando a redução de Cu(II) e Fe(III) e favorecendo assim a geração de espécies reativas de oxigênio no processo Fenton. Este catalisador propiciou a completa degradação de 200 μg L-1 de 5-FU sob radiação solar após 20 min e após 40 min no escuro, com eficiência de degradação mantida acima de 90% até o quarto ciclo de reuso na presença de 10 mmol L-1 de H2O2 e 0,5 g L-1 de HDL. O excelente desempenho de CuMgFe-B(OH)4 na degradação de 5-FU, motivou os estudos para a aplicação deste catalisador na degradação simultânea dos antibióticos sulfametoxazol (SMX), ciprofloxacina (CIP), cefalexina (CFX) e amoxicilina (AMX) e inativação dos patógenos Escherichia coli e Enterococcus faecalis com diferentes oxidantes, H2O2, PDS e PMS. Em cada sistema com os diferentes oxidantes, CuMgFe-B(OH)4 se comportou diferente. O PMS ativado pelo HDL foi o processo mais eficiente e proporcionou mais de 90% de remoção de todos os antibióticos após 120 min e inativação completa dos patógenos usando 0,5 g L-1 de HDL e 4 mmol L-1 de PMS. Entretanto, o sistema HDL com H2O2 foi eficiente para a desinfecção, mas não para a degradação de antibióticos devido à formação de complexos entre os cátions presentes na estrutura do catalisador e H2O2. O sistema ativado por PDS ocorre por uma via não radicalar envolvendo principalmente oxigênio singlete e Cu(III) com remoção de antibióticos, mas com capacidade de desinfecção limitada para Enterococcus faecallis. Nos experimentos realizados nesta tese, observou-se uma elevada estabilidade dos HDLs sintetizados e um excelente desempenho em condições neutras, o que é importante para a aplicação destes materiais como catalisadores.
Processo Fenton heterogêneo baseado em hidróxidos duplos lamelares para o tratamento de efluente urbano
Keywords: Wastewater purification; Layered double hydroxides; Disinfection; Catalysts; Environmental recovery and remediation